SARANA PRASARANA DAN LINGKUNGAN BELAJAR DALAM MANAJEMEN KESISWAAN DI RA AL HIKMAH KWEDEN KEDIRI - Zahara Violina Afya'; Muhammad Yasin (MPI STAI Sangatta Kutai Timur, 2025)
This study aims to describe the role of educational facilities, infrastructure, and the learning environment in supporting student management and human resources at RA Al Hikmah Kweden. The research focuses on how the availability, utilization, and management of educational facilities, along with the condition of the learning environment, contribute to the effectiveness of teaching and learning processes as well as students’ holistic development. This research employed a qualitative approach, using literature review, observation, and interviews with the head of RA Al Hikmah Kweden as data collection techniques. The findings indicate that the educational facilities—both consumable and durable, movable and immovable—are managed effectively to support daily learning activities. The learning environment at RA Al Hikmah Kweden is also categorized as conducive, both physically and socially, and is strengthened by a strong religious atmosphere. Although certain limitations remain, such as classroom sizes below the ideal standard and limited outdoor space, learning activities continue to run effectively due to adequate facility support and well-organized student management. Thus, the synergy between well-managed facilities and a conducive learning environment becomes a crucial factor in improving educational quality and supporting students’ academic and non-academic development at RA Al Hikmah Kweden. This study implies that RA Al-Hikmah Kweden needs to manage its infrastructure in a more planned manner, including inventory, regular maintenance, and the addition of facilities according to student growth needs. Furthermore, other PAUD institutions can use the results of this study as a reference that infrastructure management is not only understood as technical support, but is part of a student management strategy that influences children's motivation, comfort, and learning experience.